The Father’s Part: A Pilot Evaluation of a Father-Centered Family Intervention Group in Child and Adolescent Psychiatry - Mestermann, Stefan; Kleinöder, Jonas; Arndt, Marie; Krämer, Josef; Eichler, Anna; Kratz, Oliver (Behavioral Sciences, 2024)
Changes in parental roles have renewed the focus on a father’s involvement in an offspring’s psychological development. However, fathers are still under-represented in family research. There are only a few structured father-centered intervention programs in child and adolescent psychiatry. In a German population sample, a pilot father-centered family intervention program with n = 16 participants, conducted in person (n = 8) and online (n = 8), in a child and adolescent psychiatry inpatient/day clinic setting was evaluated by comparing paternal stress, PSE, and child-rated paternal competence in a pre–post design. Participating fathers showed significant decreases in child-related parenting stress (presence: p = 0.042, online: p = 0.047) and significant increases in PSE (p = 0.006/0.012). Parent-related stress and child-rated paternal competence were unaffected (p = 0.108/0.171; p = 0.167/0.101), while small-to-medium effect size measures pointed in the direction of our hypothesis (d = 0.48/0.36; d = 0.37/0.50). Participant satisfaction was higher in person than online (p = 0.008). As social and biological fathers have important influences on child and adolescent well-being and development, they should be included more frequently in prevention and intervention programs. Fathers seem to benefit from gender-specific intervention programs with regard to stress reduction, as well as experiencing competence- and PSE-increasing effects.
CRIS-Team Scopus Importer:2024-03-08
Keywords: child development; parent-centered interventions; parental behavior; parenting stress; parent–child-relation